IMPLEMENTATION OF THE PEKKAE MARKET LEVY ON REGIONAL ORIGINAL INCOME (PAD) IN TANETE RILAU DISTRICT, BARRU DISTRICT - Samsibar Samsibar; Nurlia Nurlia; Widyawati Mustan (Sean Institute, 2023)
This research aims to determine the application of pekkae market levies to regional original income and the dominant factors affecting market levies. Data sources were obtained through interviews, observation and documentation. The results of this research show that the application of the pekkae market levy on Regional Original Income in Tanete Rilau sub-district, Barru Regency includes market levies used for development within the market such as stalls, kiosks facilitated by the government which is taken from the levy. market. The dominant factors in market retribution are the principle of justice, the principle of certainty, the principle of feasibility and economic principles.